2009
DOI: 10.1080/08982100902805475
|View full text |Cite
|
Sign up to set email alerts
|

Protein adsorption and displacement at lipid layers determined by total internal reflection fluorescence (TIRF)

Abstract: In many drug delivery systems such as liposomes, the adsorption of interstitial proteins upon administration can have a huge effect on the elimination, release, and stability of the delivery system. For example, it is assumed that PEGylated liposomes prevent the adsorption of opsonins and thereby prolong the circulation time in vivo, and EMEA guidelines recommend that more than 80% of the protein antigen is adsorbed in the formulation of adjuvant systems. However, few methods exist to elucidate this protein ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In the field of pharmaceutical sciences, the emergence of proteins and peptides as powerful therapeutics has led to a renewed interest in protein adsorption in connection to e.g. chromatography and drug delivery systems; including nanocarriers, liposomes, chitosan films and polymeric systems . Understanding of protein adsorption is vital to the development of efficient analytical methods and advanced drug delivery systems and there is therefore a need for physicochemical adsorption models for interpreting results and ultimately for accurate predictions.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of pharmaceutical sciences, the emergence of proteins and peptides as powerful therapeutics has led to a renewed interest in protein adsorption in connection to e.g. chromatography and drug delivery systems; including nanocarriers, liposomes, chitosan films and polymeric systems . Understanding of protein adsorption is vital to the development of efficient analytical methods and advanced drug delivery systems and there is therefore a need for physicochemical adsorption models for interpreting results and ultimately for accurate predictions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that TIRF has the capacity to show the adsorption of proteins and peptides to lipids in SLBs (Fox et al 2009;Jorgensen et al 2009). TIRF was combined with singleparticle tracking to show the enrichment of GPI-anchored proteins in sphingolipid rich regions, as proposed by lipid raft theory Membrane curvature, exocytosis, and endocytosis are some other topics in which TIRF is successfully applied (Merrifield et al 2002(Merrifield et al , 2005Byrne et al 2008;Nagamatsu and Ohara-Imaizumi 2008;Joselevitch and Zenisek 2009; Ohara-Imaizume et al 2009;Aoki et al 2010;Gorg et al 2010;Lam et al 2010).…”
Section: Tirf Applications On Membrane Dynamicsmentioning
confidence: 99%
“…Recently, it has been shown that TIRF has the capacity to show the adsorption of proteins and peptides to lipids in SLBs (Fox et al 2009;Jorgensen et al 2009). TIRF was combined with singleparticle tracking to show the enrichment of GPI-anchored proteins in sphingolipid rich regions, as proposed by lipid raft theory (Pinaud et al 2009).…”
Section: Tirf Applications On Membrane Dynamicsmentioning
confidence: 99%
“…6 C, D). Even though the adsorption studies showed that LYS-100 was fully adsorbed to CAF®01, interstitial proteins at the SOI might compete for the binding to the cationic liposome and displace Ag more readily when more Ag is present [35] , [42] . Thus, the higher dose of Ag results in more Ag being displaced after immunization, indicating that non-adsorbed Ag draining to the LNs is favorable for B cell activation.…”
Section: Discussionmentioning
confidence: 97%